73+4y-33=15y-9-4y

Simple and best practice solution for 73+4y-33=15y-9-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 73+4y-33=15y-9-4y equation:


Simplifying
73 + 4y + -33 = 15y + -9 + -4y

Reorder the terms:
73 + -33 + 4y = 15y + -9 + -4y

Combine like terms: 73 + -33 = 40
40 + 4y = 15y + -9 + -4y

Reorder the terms:
40 + 4y = -9 + 15y + -4y

Combine like terms: 15y + -4y = 11y
40 + 4y = -9 + 11y

Solving
40 + 4y = -9 + 11y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11y' to each side of the equation.
40 + 4y + -11y = -9 + 11y + -11y

Combine like terms: 4y + -11y = -7y
40 + -7y = -9 + 11y + -11y

Combine like terms: 11y + -11y = 0
40 + -7y = -9 + 0
40 + -7y = -9

Add '-40' to each side of the equation.
40 + -40 + -7y = -9 + -40

Combine like terms: 40 + -40 = 0
0 + -7y = -9 + -40
-7y = -9 + -40

Combine like terms: -9 + -40 = -49
-7y = -49

Divide each side by '-7'.
y = 7

Simplifying
y = 7

See similar equations:

| 206Q*.2Q^2=0 | | x+21+2x=18-2x-21 | | (206-.2Q)Q=0 | | 3(y-16)+1=-5 | | 6y+3-3y=27 | | 18-6x=7+5 | | 0.19/1.577 | | -8v+28.9=3.3 | | -14.6=-2.1+w/5 | | 4x+3x-9x=60-2x-13 | | 8+x/17.92=15 | | 3x-6[4x+2(x+1)]=-12 | | 5x+138=11x-6 | | 3v-2.6=2.2 | | -3.6=v/4+9.2 | | 7.68=3u | | 0.5714x-5=3 | | 7=w/22.4 | | 4x-15=3-5x | | 2x^2-18x=-16 | | 0.8x+6.1=1.7 | | x/-5=10 | | 8-7x-2=-6+4x-10 | | 7p-2(3p+4)= | | 3x-6-4x-12=2x | | 4y-2(y-2)+5= | | 4x+18=3+8x-5 | | |-6|-|10-3|= | | 1/2+(-5/8) | | 2x+9=-97-10x | | 2/3p+1=-7 | | 5-2x+x=-10 |

Equations solver categories